Penentuan Sisa Umur Pakai Conveyor E pada Tambang Batubara PT GHI di Kabupaten Tapin, Provinsi Kalimantan Selatan - Anggi Maulana; Elfida Moralista; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Conveyor is a tool used in mining to move material from one place to another efficiently, for example coal. The conveyor has a steel-based structure that can experience corrosion. Corrosion is a threat to the conveyor structure because it can cause losses and damage to the conveyor equipment. The purpose of this research is to determine the type of corrosion, corrosion rate, remaining service life and corrosion control methods on the conveyor structure.The methodology used in this study is measuring the thickness reduction of the conveyor structure. This research was conducted on a conveyor structure of 91 meters above ground level. Measurement of the thickness of the conveyor structure using the Ultrasonic Thickness Gauge TT 130. The environmental conditions in the study area from 2016 to 2020 have air temperatures ranging from 30.880C - 37.230C, rainfall ranging from of 149,1 – 223,8 mm/year and humidity ranging from of 90.59% - 91 ,57%. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method applied to the conveyor structure is the coating method with a three layer system, namely the primary coating of Seaguard 5000, Intermediate coating of Sherglass FF and top coating aliphatic acrylic modified polyurethane. The corrosion rate of the conveyor structure is in the range of 0,1675 – 0,3000 mm/year which is included in the good category based on the relative corrosion resistance of steel. The service life of the conveyor structure is 8 years and the remaining service life ranges from 6.17 to 9.94 years. Thus, here are 28% of the predicted test points that cannot reach the design life of 15 years. Abstrak. Conveyor merupakan alat yang digunakan dalam bidang pertambangan untuk memindahkan material dari satu tempat ke tempat lain secara efisien contohnya batubara. Conveyor memiliki struktur berbahan dasar logam yang dapat mengalami korosi. Korosi merupakan salah satu ancaman bagi struktur conveyor karena dapat menyebabkan kerusakan dan kerugian pada alat conveyor. Tujuan dilakukannya penelitian ini yaitu untuk mengetahui jenis korosi, laju korosi, sisa umur pakai dan metode pengendalian korosi pada struktur conveyor. Metodologi yang digunakan dalam penelitian ini yaitu pengukuran pengurangan ketebalan struktur conveyor. Penelitian ini dilakukan pada struktur conveyor sepanjang 91 meter yang berada di atas permukaan tanah. Pengukuran ketebalan struktur conveyor menggunakan alat ultrasonic thickness gauge TT 130 pada 25 test point. Kondisi lingkungan di daerah penelitian pada tahun 2016 sampai 2020 memiliki temperatur udara berkisar antara 30,880C - 37,230C, curah hujan rata-rata berkisar antara 149,1 – 223,8 mm/tahun dan kelembaban relatif rata-rata berkisar antara 90,59% – 91,57%. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Metode pengendalian korosi yang diaplikasikan pada struktur conveyor dengan menggunakan metode coating sistem three layer yaitu primer coating Seaguard 5000, Intermediate coating Sherglass FF dan top coating aliphatic acrylic modified polyurethane. Laju korosi struktur conveyor berkisar antara 0,1675 - 0,3000 mm/tahun dan termasuk ke dalam kategori good berdasarkan ketahanan korosi relatif baja. Umur pakai struktur conveyor yaitu 8 tahun dan sisa umur pakai berkisar antara 6,17 – 9,94 tahun. Dengan demikian terdapat 28% test point yang diprediksi tidak dapat mencapai umur desainnya yaitu 15 tahun.